ACTUALIZATION OF UKRAINIAN NATIONAL WORLD OUTLOOK CODES AS THE PRECONDITION OF WORLDVIEW TRANSFORMATIONS IN THE CONDITIONS OF “HYBRID WARS” - Deviatko, Nataliia V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
The article examines the national worldview codes as a prerequisite for national revival. The urgency of studying world outlook codes in modern Ukraine is primarily due to the actualization of powerful manipulative anti-Ukrainian processes that often take the form of “hybrid wars”. The purpose of the article is to show how and based on what principles the main national world outlook codes function during important historical transformations. For this purpose, the article investigates two information and cultural fields, which are based on world-view structures of the mythological type – national and imperial myths. These structures have their branched code systems, which are updated and described in the form of mythology, symbols and signs. Two important issues are additionally considered: encoding information through the codes of other systems and the use of different languages for transmitting the message, which may cause its distortion. The components of Ukraine’s image as the main mythological image with the national code base are analyzed. Much attention is paid to describing the basic code in the national unconscious of the Ukrainian people and its differences from the imperial view of the world. The historical retrospective is depicted on the example of the “Cossack era”, the activities of the “Central Council”, the “Time of Independence”, the “Orange Revolution – 2004”, the “Dignity Revolution – 2013–2014”, military operations in the ATO-zone, etc. Modern examples show the influence of actualization of relevant world outlook codes on political, social, and cultural life. The mechanisms of combining and enhancing world outlook codes, actualized in various spheres – politics, religion, culture, in particular, mass culture, social life – are discussed. The author also considers the distribution of influence of these codes on other areas of life (up to domestic realities) for describing the surrounding world by ordinary citizens. The idea of three waves of national revival in modern Ukraine is proposed. Attention is drawn to the possible risks of ceasing the nation-building processes in the present, as well as numerous perspectives should this “wave” be as productive as possible.